STRATEGI GURU DALAM MERANCANG PEMBELAJARAN BAGI SISWA SLOW LEARNER DI SDN WIROPATEN SURAKARTA - Aftiy Diya Almala (JPI (Jurnal Pendidikan Inklusi), 2025)
This study describes the teacher's strategy in designing learning for slow-learning students at SDN Wiropaten Surakarta. The qualitative research method is data collection through interviews and observations. The research subjects included class teachers, special assistant teachers, and slow learner students. The results showed that teachers implemented various strategies, including modifications to time allocations, learning materials, and teaching and learning processes. Time allocation is modified by providing additional time outside of class hours. Learning materials are modified by simplifying the material and using visual media. Teachers pay special attention to the teaching and learning process and create an inclusive environment. The results also highlighted the cognitive, language, and socio-emotional aspects of slow-learning students. Students have difficulty understanding the material, but still try to focus. Some students experienced problems in reading due to a lack of support at home. However, social interaction in the classroom went well without discrimination. This study concludes that teacher strategies and environmental support positively affect slow learners' learning. This study recommends the need for teacher training, parental support, and an inclusive environment to improve the quality of learning. Keywords: Inclusive Education, Slow Learner, Learning Strategy